Development of Problem-Based Comic Book as Learning Media for Improving Primary School Students’ Critical Thinking Ability - Yonanda, Devi Afriyuni; Yuliati, Yuyu; Saputra, Dudu Suhandi (Mimbar Sekolah Dasar, 2019)
This research is motivated by the lack of teachers' ability to use media related to the students environment as teaching materials to develop primary school students' critical thinking ability. The research aims at developing problem-based learning media (PBL) using comic book in order to improve students' critical thinking ability. The research employed a research and development design using the experimental research design with a one-group pretest-posttest design. The subjects of the research were 28 fourth-grade students in one of primary schools in Indramayu Regency. The research produced a product in the form of problem-based comic media developed based on the needs of teachers and students. The subject material in the comic book contained problems that occurred in the real environment within the students. Based on the validation tests carried out by material experts, media experts and practitioners, the results revealed that the product was included in the “Very Valid” category. While, the practicality test results revealed that the product was included in the “Very Practical”.